Kadar Debu Terhirup Menurunkan Kapasitas Vital Paru-Paru Tenaga Kerja Iron Candle - Sudarmanto, I Gede; Purna, I Nyoman; Suyasa, I Nyoman Gede; Jirna, I Nyoman; Posmaningsih, D.A.A (Poltekkes Kemenkes Denpasar, 2022)
Dust particles are a collection of compounds in the form of solid or liquid which are scattered in the air with a very small diameter, less than 1 micron to a maximum of 500 microns. The size of dust particles that are harmful to health generally ranges from 0.1 microns to 10 microns. The dust particles will be in the air for a relatively long time in a hovering state. The work of crafting candle holders (iron candles), in the production process, allows for accidents and occupational diseases to arise from the stages of the manufacturing process. At the stage of the production process in the sanding room, a lot of dust is produced. There are workers in this section when working, some use masks and some do not. Even those who use masks are carried out infrequently, if by chance there is an inspection from the Regional Government or from the local Ministry of Manpower. The work environment is classified as hazardous to the health of the workers because dust particles can enter the body through the respiratory tract. A case control study has been conducted on 48 male and female workers at four iron candle craft companies in Tabanan district for 6 months, which is divided into 24 case groups and 24 control groups taken by cluster random sampling. The variables measured were the level of inhaled dust and the vital capacity of the workers' lungs. Analysis with the t-Paired test showed that there was a high causal relationship (significance) between the level of dust inhaled in the sanding work environment of the iron candle craft business in Tabanan district and the decrease in vital lung capacity of male and female workers.Keywords: Dust Content, Lung Vital Capacity.